Evaluation of Serum Fibrinogen, Plasminogen, α2-Anti-Plasmin, and Plasminogen Activator Inhibitor Levels (PAI) and Their Correlation with Presence of Retinopathy in Patients with Type 1 DM - Sefika Burcak Polat; Nagihan Ugurlu; Fatma Yulek; Huseyin Simavli; Reyhan Ersoy; Bekir Cakir; Ozcan Erel (Journal of Diabetes Research)
Background. Diabetic retinopathy (DR) is the leading cause of blindness in the world. Retinopathy can still progress despite optimal metabolic control. The aim of the study was to determine whether different degrees of DR (proliferative or nonproliferative) were associated with abnormally modulated hemostatic parameters in patients with T1DM. Method. 52 T1DM patients and 40 healthy controls were enrolled in the study. Patients were subdivided into three categories. Group I was defined as those without retinopathy, group II with NPRP, and group III with PRP. We compared these subgroups with each other and the control group (Group IV) according to the serum fibrinogen, plasminogen, alpha2-anti-plasmin (α2-anti-plasmin), and PAI. Results. We detected that PAI-1, serum fibrinogen, and plasminogen levels were similar between the diabetic and control groups (P=0.209, P=0.224, and P=0.244, resp.), whereas α2-anti-plasmin was higher in Groups I, II, and III compared to the control group (P<0.01, P<0.05, and P<0.001, resp.). There was a positive correlation between serum α2-anti-plasmin and HbA1c levels (r=0,268, P=0.031). Conclusion. To our knowledge there is scarce data in the literature about α2-anti-plasmin levels in type 1 diabetes. A positive correlation between α2-anti-plasmin with HbA1c suggests that fibrinolytic markers may improve with disease regulation and better glycemic control.